MUZARA’AH PADA USAHA PERTANIAN PADI: ANALISIS NILAI-NILAI ISLAMI DAN KEUANGAN - Puspitasari, Novi; Bela, Selvi Rias; Prasetiyaningtiyas, Susanti (BISMA: Jurnal Bisnis dan Manajemen, 2020)
The purpose of this study is to deeply explore the cooperation system in paddy farming in Bangsalsari District Jember. This study uses a positivist paradigm with a qualitative method and case study approach. Research informants were collected from the snowball sampling method, consisting of 4 landowners and 4 sharecroppers. The results showed that the cooperation system was manifested in the muzara’ah contract. This study found that the Islamic values implemented in the muzara’ah business practice were consisted of not doing the despotic act, being fair and trustworthy, and implementing profit sharing and halal principles. This study designed a model of business cooperation based on revenue sharing. This study also conducted a financial analysis by calculating the net agricultural income and the value of the revenue sharing for the landowners and the farmers. Keywords: cooperation, financial calculations, Islamic values, muzara'ah contract